Combined Experimental and Theoretical Investigation on Formation of Size-Controlled Silver Nanoclusters under Gas Phase - Chuhang Zhang (Biosensors, 2022)
Metallic nanoclusters (NCs) have been predicted to achieve the best Surface-Enhanced Raman Scattering (SERS) due to the controllable amount of atoms and structures in NCs. The Local Surface Plasmon Resonance (LSPR) effect on silver metal NCs (Ag<semantics>n</semantics>) enables it to be a promising candidate for manipulating the LSPR peak by controlling the size of NCs, which in turn demands a full understanding of the formation mechanism of Ag<semantics>n</semantics>. Here, we apply an extended Smoluchowski rate equation coupled with a fragmentation scheme to investigate the growth of size-selected silver NCs generated via a modulated pulsed power magnetron sputtering (MPP-MSP). A temperature-dependent fragmentation coefficient D is proposed and integrated into the rate equations. The consistency between the computational and experimental results shows that in relative low peak power (<semantics>Pp≤800</semantics> W), the recombination of cation and anion species are the dominant mechanism for NC growth. However, in the higher <semantics>Pp</semantics> region (≥800 W), the fragmentation mechanism becomes more impactful, leading to the formation of smaller NCs. The scanning electron microscopy observation shows the Ag<semantics>36</semantics> is successfully soft-landed and immobilized on a strontium titanate crystal, which facilitates the application of the Ag<semantics>n</semantics>/STO to the SERS research.